PM.83 Testing For Fetomaternal Haemorrhage by Acid Elution Can Yield False Positive Results in the Presence of Elevated Maternal Fetal Haemoglobin. (26th April 2013) - Doyle, A; Donnelly, J; Campbell, S; Murphy, D; Corcoran, D; Kumpel, B; Ainle, FD Ni
Abstract : Appropriate testing for fetomaternal haemorrhage (FMH) is critical in the prevention of morbidity and mortality due to haemolytic disease of the fetus and newborn (HDFN) in RhD negative women. The Kleihauer or acid elution (AE) test is widely used to assess the size of fetomaternal haemorrhage and to determine whether sufficient Anti-D immunoglobulin has been administered to prevent HDFN. This test is based on the principle that adult haemoglobin (HbA) is eluted from red cells in an acidic solution while the fetal haemoglobin (HbF) is not. However, in the presence of an elevated level of HbF of maternal origin, the AE test may be "positive" in the absence of a true FMH. We report two cases in which this situation arose antenatally, leading to difficulties in clinical interpretation. In both cases, specialised flow cytometry revealed the presence of elevated levels of HbF of maternal origin. While awaiting completion of specialised investigations, Anti-D was administered but was later found to have been unnecessary. Early awareness of the possibility of elevated maternal F cells ensures that samples can be sent to appropriate reference laboratories early to limit unnecessary Anti-D administration. The true prevalence of "false positive" AE tests due to elevated maternal HbF is unknown and is the subject of ongoing work in our laboratory, but should be considered in the differential diagnosis of an AE test remaining positive despite appropriate Anti-D administration.